Pengaruh Pengendalian Internal Terhadap Indikasi Fraud Berdasarkan Teori Fraud Octagon Pada Perbankan - Rizky Fajar, Abdul; Novita, Novita (Sekolah Tinggi Ilmu Ekonomi Mahaputra Riau, 2026)
This study aims to analyze the effect of internal control on fraud indications by employing the Fraud Octagon Theory as an analytical framework, with a focus on the banking sector through a case study at Bank X. Fraud in the banking industry represents a critical issue that threatens both financial stability and institutional reputation. The Fraud Octagon Theory, which encompasses eight elements pressure, opportunity, rationalization, arrogance, competence, ego, personal need, and moral consistency—serves as the basis for identifying factors that may trigger fraudulent behavior. The research adopts a quantitative method with descriptive and verification approaches. Data were collected through questionnaires distributed to employees working in the operational units of Bank X, and were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate both direct and indirect relationships between internal control and fraud indications. The findings reveal that internal control significantly influences fraud indications. A stronger internal control system is associated with reduced opportunities for fraudulent acts, while dimensions of the Fraud Octagon particularly pressure and rationalization emerge as critical mediating factors that reinforce this relationship. These results emphasize the necessity for a structured, adaptive, and sustainable internal control system in mitigating the evolving risks of fraud within the banking sector.